Innovation in Civics Learning to Strengthen National Values Through Digital Pianica Music in Elementary Students - Cahyanisam, Clarista; Kumalasari, Indah; Wijayanto, Wasis (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to describe the process and impact of innovative learning of Pancasila and Citizenship Education (PPKn) through digital music media using the song "Garuda Pancasila" with a digital pianica. The background of this study is the low enthusiasm and involvement of students in PPKn learning which is conventional and tends to be monotonous. Research Methods: A descriptive qualitative approach was used in this study with data collection techniques in the form of observation, interviews, documentation, and literature studies. The subjects of the study were 25 fourth-grade students of SD Negeri 2 Sukolilo. Finding/Results: The results of the study showed that the use of national songs in PPKn learning was able to improve students' understanding of national values cognitively, affectively, and psychomotorically. Learning became more lively, fun, and collaborative. In addition, playing music activities formed cooperation, empathy, and a sense of responsibility for students in groups. Although there were challenges in implementation, such as limited musical instruments and teacher skills, collaborative solutions between teachers, schools, and parents were able to support successful implementation. Conclusion: The integration of art and technology in PPKn learning has proven to be effective and relevant for instilling national character from an early age.